2012 19th IEEE International Conference on Image Processing 2012
DOI: 10.1109/icip.2012.6467401
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for transform selection in multiple-transform video compression

Abstract: Selecting proper transforms for video compression has been based on the rate-distortion criterion. Transforms that appear reasonable are incorporated into a video coding system and their performance is evaluated. This approach is tedious when a large number of transforms are used. A quick approach to evaluate these transforms is based on the energy compaction property. With a proper transform, an image or motioncompensated residual can be represented quite accurately with a small fraction of the transform coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The first algorithm, it's simple, obtains local optimal solution. The second algorithm, it's computationally intensive, obtains globally optimal solution [19].…”
Section: Literature Surveymentioning
confidence: 99%
“…The first algorithm, it's simple, obtains local optimal solution. The second algorithm, it's computationally intensive, obtains globally optimal solution [19].…”
Section: Literature Surveymentioning
confidence: 99%
“…Energy compaction can be defined as the ability to pack a large fraction of signal energy into just a few transform coefficients. The research in [3] presents the increase in energy compaction capability of the video compression system when 1D directional transforms are added for compression of MC residuals. It is reported that using 1D directional transforms and 2D DCT instead of using only 2D DCT significantly increases preserved energy.…”
Section: Auto-covariance Analysis Of MC Residualmentioning
confidence: 99%
“…In the framework of existing hybrid video coding, the modules mainly consist of intra/inter prediction, transform, quantization, entropy encoding and in-loop filtering. To improve compression efficiency, a variety of novel coding tools have been developed in the issued standards, including QuadTree plus Multi-Type Tree (QT+MTT) structure [16] for coding block partition, Matrixbased Intra Prediction (MIP) [31] and Cross-Component Linear Model (CCLM) [43] for intra luma and chroma prediction, History-based Motion Vector Prediction (HMVP) [44] and Decoder-side MV Refinement (DMVR) [14] for motion estimation/compensation, Multiple Transform Selection (MTS) [8] for transform, CABAC engine with multi-hypothesis probability estimation for entropy encoding, Sample Adaptive Offset (SAO) and Adaptive Loop Filter (ALF) for in-loop filtering. These mentioned coding tools have achieved significant coding gains.…”
Section: Introductionmentioning
confidence: 99%